Determinants of Contact Dermatitis Among Fishermen: A Study on Barrang Lompo Island, Indonesia - Iqrayati Kasrudin; Agus Bintara Birawida; Hasnawati Amqam; Anwar Daud; Muhammad Rachmat; Stang Stang; Syamsiar R. Russeng; Gurendro Putro; Nurlia Sila (Journal of Public Health and Pharmacy, 2025)
Introduction: Contact dermatitis is a common health issue among fishermen caused by exposure to harsh working environments, including seawater, chemicals, and suboptimal use of personal protective equipment (PPE). Factors such as personal hygiene, history of skin diseases, and access to clean water can influence the incidence of contact dermatitis. The novelty of this study is combining environmental sanitation and occupational health factors of fishermen that influence contact dermatitis, which have previously been studied only partially. The results of this study also found that the PPE (Personal Protective Equipment) variable acts as a moderating factor influencing contact dermatitis. This study aims to investigate the causal relationships between personal hygiene, history of skin diseases, PPE use, and access to clean water with the incidence of contact dermatitis among fishermen on Barrang Lompo Island. Methods: This study employed a cross-sectional using Structural Equation Modeling (SEM) to analysed the relationships between personal hygiene, skin disease history, PPE use, and access to clean water. SEM effectively evaluates interactions among latent variables, offering a robust approach to occupational health issues and providing insights into how individual and environmental factors influence dermatitis prevalence. Data were collected through structured interviews and validated questionnaires. Results: The analysis showed that personal hygiene and history of skin diseases had significant relationships with the incidence of dermatitis (p < 0.05). However, PPE use and access to clean water did not show a significant direct effect. Conclusion: Improving personal hygiene practices and targeted interventions for individuals with a history of skin diseases are essential for reducing contact dermatitis among fishermen. Education on proper hygiene techniques and optimizing PPE use are recommended for maximum protection.